Decision of Vietnam's Minister of Agriculture acknowledging Alternate Wetting and Drying (AWD) suitability mapping methodology as one of the ministerial-level initiatives - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The Minister of Agriculture recognised the scope of influence of the AWD suitability mapping methodology for low-emission rice production and that AWD can bring practical benefits to Vietnam's agriculture sector.